2020
DOI: 10.3390/polym12102210
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Scaffolds Fabricated via 3D Printing and Salt Leaching: In Vivo Imaging, Biodegradation, and Inflammation

Abstract: In this work, we prepared fluorescently labeled poly(ε-caprolactone-ran-lactic acid) (PCLA-F) as a biomaterial to fabricate three-dimensional (3D) scaffolds via salt leaching and 3D printing. The salt-leached PCLA-F scaffold was fabricated using NaCl and methylene chloride, and it had an irregular, interconnected 3D structure. The printed PCLA-F scaffold was fabricated using a fused deposition modeling printer, and it had a layered, orthogonally oriented 3D structure. The printed scaffold fabrication method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…An ideal strategy is to use natural bioactive molecules to integrate into scaffolds, giving them multifunctional properties 24 . Polymerization of caprolactone and lactide (PCLA) is a macromolecular copolymer prepared by bulk ring‐opening polymerization of caprolactone (PC) and lactide (LA) monomers and has been exploited for medical application via controllable temperature‐sensitive hydrogel or drug delivery capsules 25,26 . The degradation rate of the copolymer could be controlled by the monomer and reduces the acidity of the degradation products, which is an ideal scaffold for bone support and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ideal strategy is to use natural bioactive molecules to integrate into scaffolds, giving them multifunctional properties 24 . Polymerization of caprolactone and lactide (PCLA) is a macromolecular copolymer prepared by bulk ring‐opening polymerization of caprolactone (PC) and lactide (LA) monomers and has been exploited for medical application via controllable temperature‐sensitive hydrogel or drug delivery capsules 25,26 . The degradation rate of the copolymer could be controlled by the monomer and reduces the acidity of the degradation products, which is an ideal scaffold for bone support and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“… 24 Polymerization of caprolactone and lactide (PCLA) is a macromolecular copolymer prepared by bulk ring‐opening polymerization of caprolactone (PC) and lactide (LA) monomers and has been exploited for medical application via controllable temperature‐sensitive hydrogel or drug delivery capsules. 25 , 26 The degradation rate of the copolymer could be controlled by the monomer and reduces the acidity of the degradation products, which is an ideal scaffold for bone support and cell adhesion. The acicular nano‐hydroxyapatite (HA) can increase additives' biomineralization and cell proliferation ability.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques can be used to create the best environment for the cartilage regeneration. Several studies have revealed gas foaming, salt leaching, solvent casting, or 3D printing as effective techniques for scaffold formation [13][14][15]. Electrospinning, for instance, provides a possibility to generate loosely connected mattes with different thickness of continuous fibers [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the limitations of sc-foaming are related to the complex modelling of the pore formation mechanisms to get a precise control and predictability of the pore sizes and distributions obtained for the processed scaffolds. Moreover, the use of depressurization gradients [ 18 ] and leaching methods with particulate porogens (e.g., NaCl, sucrose, carbonates, bicarbonates, zein [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]), and sacrificial polymers [ 27 ] within this foaming process can result in scaffolds with more open porosity and dual macroporosity (i.e., porous materials with two pore families in the macroporous range) [ 19 , 28 ]. The use of porogens is the most suitable approach to reach an additional macropore family with well-defined porosity and narrow pore size distribution, although an extra processing step will be usually needed to remove the porogen by solvent (usually water) leaching and the advantageous solvent-free property of sc-foaming technique is thus omitted [ 12 , 29 ].…”
Section: Introductionmentioning
confidence: 99%